Overview of Work Stress of Medical Record Officer of Distribution Section at RSUP H. Adam Malik Medan - Lubis, Siti Permata Sari (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2023)
Work stress can be experienced by everyone without exception workers in hospitals and is a consequence of workplace events that demand excessive physical and psychological involvement of employees (Triatna, 2015). Work stress that lasts continuously can cause emotional and behavioral changes such as irritability and difficulty concentrating, which can reduce one's work motivation and result in a decrease in work quality The purpose of this study is to determine the picture of work stress of distribution medical record officers at H. Adam Malik Hospital Medan. The type of research conducted is qualitative descriptive. The sample used by researchers took all 5 distribution officers. Research variables are an attribute or trait of people who have certain variations set by researchers, research instruments in the form of questionnaires given to respondents to see the picture of work stress of medical record officers in the distribution section. Data analysis in this study is presented in the form of a distribution table. The results of research conducted on 5 respondents that the majority of work stress can be concluded that as many as 4 respondents (80%) experience work stress, and the minority work stress as many as 1 respondent (20%). From the results of the study above, it can be concluded that the description of work stress of distribution medical record officers at H. Adam Malik Hospital Medan the majority experience work stress. The researcher's suggestion to the hospital is to provide facilities in the form of goods carriers to medical record officers in the distribution department to facilitate the delivery of medical record files to the polyclinic and this can reduce the workload of medical record officers in lifting heavy items.